Czesława Miłosza zmagania z naturą - Głuszak, Michał (Motywy fauny i flory w literaturze i kulturze, 2018)
The aim of the article is to present Miłosz’s reflections on nature. It was the issue that the poet found particularly engaging. Starting from his childhood, which he spent in a manor house in the village of Szetejnie, Lithuanian nature and nature related rituals became the object of childhood’s fascination for the author of Rescue. The picturesque valley, avenue of lime trees, oak grove, hunting, picking mushrooms, celebration of Pentecost. That was what shaped the future poet and affected his sensitivity. With time, Milosz saw the darker side of nature. The inevitability of death, the unrelenting passing, brutality, tough law governing the whole of creation, according to which the stronger beats the weaker. This discovery forged a fascinating adventure in intellectual as well as literary sense. The text shows the evolution of the relationship between Miłosz and the world of nature. The relationships that is thought to be quite complex and full of ambiguity. I dedicate my consideration mainly to Miłosz’s most important novel The Issa Valley and selected works of his lyric poetry.